Multicultural Education Based On Local History Material Of The Islamic Sultanate In West Kalimantan - Mohammad Rikaz Prabowo (IJGIE (International Journal of Graduate of Islamic Education), 2023)
The development of multicultural education in post-reform Indonesia is against the backdrop of a very plural and heterogeneous region in Indonesia. It is hoped that this study can be a solution to maintain social harmony. This writing aims to describe: (1) How local content is the basis of multicultural education, (2) how history is related to multicultural education, (3) how multicultural education is taught in schools. This writing uses a form of descriptive writing through literature study related to the chosen topic. Based on the results of the data search obtained, the following conclusions can be drawn. First, local content can become a formal basis for implementing multicultural education based on history and culture as stated in the regulations of the Minister of Education and Culture. The aim is to develop students' abilities related to the environment in the social, cultural and artistic fields. Second, history has a close and intimate relationship with multiculturalism. Existing culture is the result of growth and development in the past, so to know and recognize it, it is necessary to look at history. Multicultural education is seen as a way to convey diversity, plurality and tolerance through educational channels. Third, multicultural education is in line with the development of local history studies. So that the two can fuse and then be integrated as a local charge. It is given by inserting a periodization of the history of the Islamic sultanate into history subject. Keywords: Multicultural, history, Islamic sultanate